PERAN KEARIFAN LOKAL DALAM MEMBANGUN CITRA RUMAH SAKIT : TINJAUAN LITERATUR SISTEMATIS - Rina Asih Budi Cahyaningrum Rina Asih Budi Cahyaningrum; Bayu Hartono; Intan Sekar Arumdani (LPPM Universitas Awal Bros, 2026)
​​ This study analyzes hospital image through sustainable policies that integrate local wisdom and holistic care approaches. Local wisdom-based policies are considered capable of adapting services to the community's cultural values, whereas holistic care emphasizes comprehensive treatment encompassing physical, emotional, social, and spiritual aspects. A descriptive analysis based on the Scopus database reveals that research trends using the keywords